DNA methylation meningioma biomarkers: attributes and limitations - Li, Zhaohui; Gao, Yufei; Zhang, Jinnan; Han, Liang; Zhao, Hang (Frontiers in Molecular Neuroscience, 2023)
Meningioma, one of the most common primary central nervous system tumors, are classified into three grades by the World Health Organization (WHO) based on histopathology. The gold-standard treatment, surgical resection, is hampered by issues such as incomplete resection in some cases and a high recurrence rate. Alongside genetic alterations, DNA methylation, plays a crucial role in progression of meningiomas. in the occurrence and development of meningiomas. The epigenetic landscape of meningioma is instrumental in refining tumor classification, identifying robust molecular markers, determining prognosis, guiding treatment selection, and innovating new therapeutic strategies. Existing classifications lack comprehensive accuracy, and effective therapies are limited. Methylated DNA markers, exhibiting differential characteristics across varying meningioma grades, serve as invaluable diagnostic tools. Particularly, combinatorial methylated markers offer insights into meningioma pathogenesis, tissue origin, subtype classification, and clinical outcomes. This review integrates current research to highlight some of the most promising DNA and promoter methylation markers employed in meningioma diagnostics. Despite their promise, the development and application of DNA methylation biomarkers for meningioma diagnosis and treatment are still in their infancy, with only a handful of DNA methylation inhibitors currently clinically employed for meningioma treatment. Future studies are essential to validate these markers and ascertain their clinical utility. Combinatorial methylated DNA markers for meningiomas have broad implications for understanding tumor development and progression, signaling a paradigm shift in therapeutic strategies for meningiomas.